2017
DOI: 10.1080/15388220.2017.1387128
|View full text |Cite
|
Sign up to set email alerts
|

Violence in school: An investigation of physical, psychological, and sexual victimization reported by Italian adolescents

Abstract: In Italy, numerous studies have been carried out regarding the phenomenon of bullying; however, studies on single incidences of sexual, physical, and psychological victimization at school remain scant. Therefore the aim of this study is to examine the phenomenon of scholastic violence with a broader perspective, as well as all the possible perpetrators including adults. The sample consisted of 277 adolescents (64% female), ranging from grade 6th to 13th (mean age = 13.29, SD = 2.19). Sixty-four percent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…In addition, teachers referred to social class as a possible cause of victimization. The above are in line with the findings of international and Greek literature (Andreou & Bonoti, 2010;Besag, 1989;Boulton & et al, 2001;Gotovos, 1996;Kokkinos, & Karagianni, 2017;Longobardi et al, 2017;Olweus, , 2009Rigby, 1996;Sapouna, 2008;Sullivan et al, 2004;Swearer & Doll, 2001). Teachers shape their typologies through social interaction with students, distinguishing between the characteristics of the victimizer and the victim and signifying the primary importance of the individual's social status, appearance, and interpersonal characteristics (Lamnias, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, teachers referred to social class as a possible cause of victimization. The above are in line with the findings of international and Greek literature (Andreou & Bonoti, 2010;Besag, 1989;Boulton & et al, 2001;Gotovos, 1996;Kokkinos, & Karagianni, 2017;Longobardi et al, 2017;Olweus, , 2009Rigby, 1996;Sapouna, 2008;Sullivan et al, 2004;Swearer & Doll, 2001). Teachers shape their typologies through social interaction with students, distinguishing between the characteristics of the victimizer and the victim and signifying the primary importance of the individual's social status, appearance, and interpersonal characteristics (Lamnias, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…As bullying is generally influenced by the environment and other social factors, it impacts a school at the classroom level (Longobardi, Prino, Fabris, & Settanni, , ). Every child, as a component of the group, has a role in the bullying event.…”
Section: Introductionmentioning
confidence: 99%
“…Peer victimization among adolescents is a serious social concern, and the incidence rates are growing globally ( Sullivan et al, 2006 ; Longobardi et al, 2017 ). Peer victimization is defined as a repeatedly experienced form of aggressive behavior, perpetrated within the peer group ( Hunter et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that 9–32% of adolescents in China and other countries experienced peer victimization ( Huang et al, 2013 ; Jackson et al, 2016 ; Pouwels et al, 2016 ). Ample research evidence has indicated that peer victimization is associated with a variety of negative outcomes, including poor school adjustment, and internalizing (e.g., depression) and externalizing problems (e.g., aggressive behavior; Longobardi et al, 2017 ; Noret et al, 2018 ). Therefore, understanding the mechanisms of peer victimization on adolescent development is essential for the development of protective intervention programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation